A new species of Bathynomus Milne Edwards, 1879 (Isopoda: Cirolanidae) from The Bahamas, Western Atlantic - Shipley, Oliver N.; Bruce, Niel L.; Violich, Mackellar; Baco, Amy; Morgan, Nicole; Rawlins, Scott; Brooks, Edward J. (Zootaxa, 2016)
A new species of cirolanid isopod, Bathynomus maxeyorum sp. nov., from The Bahamas, Western Atlantic, is described. This species represents the fourth species of Bathynomus to be described from the tropical and sub-tropical Western Atlantic. Bathynomus maxeyorum sp. nov. is characterized by 7 broad short pleotelsonic spines, with setation running along ~80% of the posterior margin of the pleotelson. Genetic analysis indicates a ~14% sequence divergence from the sympatric species Bathynomus giganteus.